Post-Thoracic Surgery Nursing Care: A Comprehensive Review - Kunwor, Sonia; Sapkota, Sandeep (Nepalese Journal of Cancer, 2025)
Background: Thoracic surgery, including lobectomy, pneumonectomy, and esophagectomy, is associated with significant postoperative complications such as respiratory failure, pain, wound infection, arrhythmias, and thromboembolism. This narrative review synthesizes current evidence on postoperative nursing care following thoracic surgery. Methods: A purposive search of PubMed, Google Scholar, ScienceDirect, CINAHL, and institutional resources was conducted, focusing on English-language literature published from 2014–2025. Articles addressing postoperative nursing assessment, interventions, and outcomes in thoracic surgery patients were reviewed and narratively synthesized. Results: Evidence underscores the importance of structured nursing interventions in multiple domains: systematic assessment using tools like the Modified Early Warning Score (MEWS), respiratory care with incentive spirometry and physiotherapy, multimodal pain management, aseptic wound care, and chest tube management. Early ambulation, optimized nutrition, fluid balance, psychosocial support, and patient education further contribute to enhanced recovery. Nurse-led implementation of ERAS protocols has consistently been shown to reduce pulmonary complications, shorten hospital stays, and improve overall outcomes. However, challenges remain, including limited thoracic-specific nursing assessment tools, inconsistent application of standardized care pathways, and gaps in training in low-resource environments such as Nepal. Conclusion: Postoperative thoracic care is highly dependent on skilled nursing interventions across multiple domains of recovery. Integrating ERAS principles, structured discharge planning, and nurse-led follow-up can significantly reduce complications and improve patient outcomes.